Impact of Silica Nanoparticles on the Durability of fly Ash Concrete - Ali, D.; Sharma, U.; Singh, R.; Singh, L. P. (Frontiers in Built Environment, 2021)
In the present study, the mechanical and durability properties of silica nanoparticle (SNPs) incorporated fly ash (FA) concrete mix were examined after 365 days of exposure. The dosage of FA replace with cement in the present study are 30, 40 and 50%, while, 3% SNPs was added by the weight of cement in the FA incorporated mix. For a comparison of SNPs with silica fume (SF), 6% SF was added (by the weight of cement) and entire casting was performed at constant water to binder (w/b) ratio of 0.29. The present work is the extension of previous study, wherein, durability properties of the same mixes were reported up to 180 days of exposure. Compressive strength results show that in presence of SNPs, the enhancement in compressive strength was in the range of 10-14%, while in presence of SF, 8-10% of the enhancement was observed as compared to control. However, exposed samples in carbonation environment show that compressive strength of control and SF incorporated mix was increased, while SNPs incorporated samples show negligible enhancement. Further, sulphate exposed mix show that compressive strength decreases, however, SNPs incorporated mix show lowest reduction as compared to other mixes. Therefore, the study shows that SNPs incorporated mix have higher mechanical properties and more durability as compared to other mixes in severe environment.